IMPACT OF EARLY-LIFE MICROBIOTA ON THE DEVELOPMENT OF INFANTS - N. L. Pakhomovskaya (Медицинский совет, 2018)
The article presents present-day knowledge on the impact of microbiota on the health and development of infants, and considers the process of the microflora formation in newborns. It discusses the impact of the gut microbiota on the onset and course of such pathological conditions as infant intestinal colic and necrotizing enterocolitis, and the use of probiotic preparations for the prevention and correction of dysbiotic disorders.